Condit dam removal : a decision-making comparison with removal of Elwha River dams - Wallace, Laura (Kansas State University, 2014)
While environmental concerns have played a secondary role in dam removal rationales thus far, the Condit and Elwha removal projects could signal a change in governmental and public priorities in dam management in the United States (Born et al. 1998; Bednarek 2002). For this research, I compared two dam removal projects designed to restore native salmon runs in two rivers in Washington State: the Condit Dam on the White Salmon River and the Elwha and Glines Canyon Dams on the Elwha River. This thesis asks: given choices of preserving dams that produce clean electricity and the well-established lake-based habitats created by their reservoirs or re-establishing a free-flowing river to reestablish fish and wildlife populations, how are decisions made, and what does the process and outcome mean to local communities? Research interview data was used in combination with policy documents to answer three research questions: 1) What factors affect decision-makers’ and other stakeholders’ support for (or rejection of) dam removal? 2) How did stakeholders’ perceptions and opinions play a role in the decision-making process? and 3) What can we learn from problems and successes evident from the dam removal decision processes? The main factors influencing both the Condit Project and the Elwha Project were environmental (salmon restoration), political (meeting legislative requirements for fish passage), and economic (finding the least cost fish passage alternative). The primary motivation for both projects was salmon restoration via the provision of federally mandated fish passage. The possibility of regaining a valuable resource spurred Tribal, federal, and state agencies to advocate for the removal alternative. Dam owners in both cases desired the least cost option, resulting either in their consent to removal (Condit Project) or selling the dams and relinquishing responsibility to the federal government (Elwha Project). Both took over two decades to complete and were removed in 2011. Perceptions of the relative importance of removal/retention options and dissatisfaction with the decision-making process led to polarization of the communities affected by the dam removals and contributed to the 20+ year project timelines. In order to promote good will and understanding between decision makers and stakeholders, two lessons can be learned from the Condit and Elwha Projects: 1) actively seek to include both proponents and opponents in decision-making and 2) establish robust communication among stakeholders and decision makers. Additionally, preliminary evidence indicates that dam removal does result in movement of salmonids to river reaches that had been blocked by dams, and dam removal may also lead to unintended consequences related to local environmental quality and resource access, such as short term air quality concerns and longer term effects on groundwater availability.
Keywords: environmental decision-making; perception; priorities; opinion; salmon; dam removal; Geography (0366); Natural Resource Management (0528); Social Research (0344)